A study of essential components of three types of Bituminous Materials in Mishraq sulfur Mine - Motea Al jbouri; Hala Jasim; thaer halo (College of Education for Pure Sciences, 2020)
.The chemical constituentis of three types of bituminous materials found in different conditions in Mishraq sulfur Mine was studied. The FTIR spectroscopy showed reduce in the length of hydrocarbon‏ chains from the intensity of paraffinic bands in bitumenous materials of Frasch sulfur Mine (BM) compare with natural bituminous materials (NB) and Bituminous materials which extracted in-depth about 200 m without exposing to Frasch process condition (BB). The percentage of asphaltene in (MB) which increases dramatically is found 63.64% compared with (BB) and (NB) which 37.37% and 14.28% respectively and a similar decrease in percentage petrolene (maltene) . A percentage of n-hexane fraction by silica gel chromatography of petrolene (MB) is 18.49% compared with (BB and N.B) are 25.06 % and 47.05 % respectively while the cyclohexane fractions of petrolene MB are four-time of N.B and three-time of B.B . From all results, we conclude that a reaction has occurred between sulfur and bitumenous materials especially hydrocarbon chains of Aromatics and naphthenic rings in sulfur well during Frasch process which leads to an increase in asphaltene percentage and decrease of petrolene.